Advancements and future prospects of wearable sensing technology for healthcare applications. Issue 3 (4th April 2022) - Sharma, Asha; Singh, Anoop; Gupta, Vinay; Arya, Sandeep
Abstract : The realm of wearable technology is continually growing. Abstract : The realm of wearable technology is continually growing. Researchers are encouraged to design additional wearable monitoring devices as wearable technology advances and the need for real-time analyte monitoring grows. Wearable monitoring systems are, in fact, being hailed as the next generation of personal portable electronics. Wearable healthcare systems will usher in a new era for illness detection, treatment, and prevention as material science, integrated circuit construction, innovation for manufacturing, fabrication of integrated circuits, and structural design advancement. Wearables are used in a variety of industries, including agriculture, sports, and healthcare navigation systems. The relevance of wearable devices in the area of customised healthcare is discussed in this paper, as well as their future conceptual development. The last portion includes conclusions that focus on crucial challenges and emerging developments in the realm of wearable healthcare devices.